Fast parallel DNA-based algorithms for molecular computation: determining a prime number - Weng-Long Chang; Ho, M.; Minyi Guo; Xiaohong Jiang; Jingling Xue; Minglu Li (Third International Conference on Information Technology and Applications : 4-7 July 2005, Sydney, Australia : proceedings, 2005)
This paper demonstrates that testing whether a natural number is a prime number or not can also be solved with O(k/sup 3/) biological operations, O(2/sup k/) DNA library strands, O(k/sup 2/) the longest length of DNA library and O(1) tubes, where k is the number of bits for a natural number to be checked.